PENGARUH KEPEMIMPINAN TERHADAP EFEKTIFITAS KERJA PEGAWAI DI DINAS PERHUBUNGAN KABUPATEN KUBU RAYA - Putri Utami Dini E.42008077 (GOVERNANCE, Jurnal Ilmu Pemerintahan, 2012)
The title of this study is "Effect of the effectiveness of leadership at the Department of Transportation employee Kubu Raya district. Based on the breadth of aspects of leaderships, the study was limited as the effect (function) leadership (department heads) to effective employee in the Department of Transportation District Kubu Raya. This study aimed to determine whether there is an influence on the effectiveness of leadership functions in the Department of Transportation employees work Kubu Raya district. The title of this thesis raised by the development of new institutions in Kubu Raya district is the responsibility of each department head to manage and administer the assigned positions, so that the effectiveness of the work of each agency accountable. This research is quantitative research using statistical correlation Pearson Product Moment. Based on the analysis of statistical data, indicators in this study is valid and reliable variables are. For to knoe the results of the study, to determine the relationship obtained the following results: rxy = 0.216, while to know how much influence between two variables, do pengkuadradan of the correlation coefficient, so rxy ² = 0.046656.. The results indicate that the hypothesis rxyhitung smaller than rxytabel (0.216 <0.44) with a significance level of 0.046656 or 4.66% so in this study, explained the rejection of hypotheses, there is no influence of the work function of the effectiveness of leadership, despite rejecting the hypothesis in significance of measurement data, the minimal influence of the leadership function of the effectiveness of an employee working at the Department of Transportation District Kubu Raya. Key Word : Leadership and employee effectiveness